ATITUDE, SOCIAL INFLUENCE DAN TRUST PADA BEHAVIOURAL INTENTIONS KONSUMEN MOBILE SHOPPING DI SURABAYA - Muhammad Hanif; Dudi Anandya; Silvia Margaretha (Perpustakaan Universitas Surabaya, 2021)
Abstract — This research aims to determine the influence of attitude, trust and social influence against behavioural intentions in the consumer of mobile shopping in Surabaya. This type of research is basic business research using quantitative approach with data analysis in the form of SEM (Structural Equation Model). Data processing in this study using PASW program (Predictive Analytics Software) version 18 and AMOS 22.0 for Windows used for testing the Measurement Model (Outer Model) and Structural Model (Inner Model). The sampling technique used is non probality sampling with samples of 310 respondents aged at least 16 years and above who have made purchases with mobile devices on Shopee in the last 6 months.The results of this research show that perceived ease of use, perceived enjoyment, has a positive influence on attitude toward mobile shopping. Attitude toward mobile shopping, trust in the M-Vendor, social influences has a positive influence on intentions behaviour. Keywords: trust in the m-vendor, social influences, attitude toward mobile shopping, behaviour intentions and satisfaction Abstrak— Penelitian ini bertujuan untuk mengetahui pengaruh attitude, trust dan social influence terhadap behavioural intentions pada konsumen mobile shopping di Surabaya. Jenis Penelitian ini adalah basic business research menggunakan pendekatan kuantitatif dengan analisis data berupa SEM (Structural Equation Model). Pengolahan data pada penelitian ini menggunakan program PASW ( Predictive Analytics Software) versi 18 dan AMOS 22.0 for windows yang digunakan untuk pengujian Measurement Model (Outer Model) dan Structural Model (Inner Model). Teknik pengambilan sampel yang digunakan adalah non probality sampling dengan jumlah sampel 310 responden berusia minimal 16 tahun keatas yang pernah melakukan pembelian dengan perangkat mobile pada Shopee dalam 6 bulan terakhir. Hasil penelitian ini menunjukkan bahwa perceived ease of use, perceived enjoyment, memiliki pengaruh positif terhadap attitude toward mobile shopping. attitude toward mobile shopping,trust in the m-vendor, social influences memiliki pengaruh positif terhadap behaviour intentions. Kata kunci: trust in the m-vendor, social influences, attitude toward mobile shopping, behaviour intentions and satisfaction